ANALISIS URGENSI PENGESAHAN RUU MASYARAKAT ADAT DALAM MENJAMIN KEPASTIAN HAK-HAK MASYARAKAT ADAT DI INDONESIA: KAJIAN PUSTAKA ATAS MANDEKNYA PROSES LEGISLASI HINGGA 2025 - Rengga Yudha Santoso; Krisna Bayu Pratama (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyse the urgency of passing the Indigenous Peoples Bill as an important instrument in guaranteeing legal certainty and protecting the rights of indigenous peoples in Indonesia, while also examining the factors that have caused the legislative process to stall until 2025. Using a library research method with a descriptive-analytical qualitative approach, data was obtained from legislation, Constitutional Court decisions, official government documents, reports from non-governmental organisations, and national and international academic literature. The study findings indicate that without a single legal framework, indigenous communities remain vulnerable to land grabs, criminalisation, and marginalisation due to overlapping sectoral regulations. The Indigenous Peoples Bill is of high urgency to integrate legal protection, policy consistency, and alignment with international commitments such as the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP). However, the legislative process is hindered by technical obstacles in drafting the bill, political and economic interests, weak inter-agency coordination, the dominance of industry lobbying, and a lack of effective public support. This study recommends the formation of a solid advocacy coalition, increased public awareness, harmonisation of cross-sectoral regulations, and committed political leadership to accelerate the enactment of this bill for the realisation of social justice and inclusive national development.